Analisa Pencatatan Nikah (Kawin Belum Tercatat) Pada Kk Dalam Persfektif Disdukcapil Purwakarta - Yusuf Setiawan (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2022)
KK (family card) is a very important family identity card and must be owned by every citizen. The author's purpose in this study is to answer two problem formulations, namely how the legal basis for the marriage category has not been recorded as marital status in the KK form and how the importance of legal fulfillment and protection of marriage has not been recorded as marital status on the KK blank. This research is a research using qualitative methods. Where the data analyzed is in the form of word exposure and description of the situation, not numbers. The data collection techniques used are interviews and documentation. Starting from theories that discuss marriage registration and population administration along with the data that has been collected, then further analyzed by juridical analysis using applicable laws and regulations, which are contained in Law Number 1 of 1974 concerning Marriage, Article 2 of Government Regulation Number 9 1975 concerning marriage registration, Islamic Law Compilation Book 1 of Marriage Law and Minister of Religion Regulation of the Republic of Indonesia Number 19 of 2018 concerning Marriage Registration to then draw a conclusion. The results of this study indicate that, changes in the status of marriage in the blank of the family card which originally had marital status, unmarried to registered marriage and unregistered marriage. This regulation is regulated in Minister of Home Affairs Regulation Number 118 of 2017 concerning Blank Family Cards, Registration, and Quotations of Civil Registration Deeds which was followed up with the development of SIAK 7 (Population Administration Information System version 7) by the Directorate General of Population and Civil Registration The Indonesian Ministry of Home Affairs, where one of the requirements in the population registration must attach a marriage book or marriage certificate, and for unregistered marriages can attach a Statement of Absolute Responsibility (SPTJM) the truth of marriage on the basis of clear considerations in accordance with the study of cases of family problems in Indonesia. society, human rights, rights of citizens, civil law, the mandate of the 1945 Constitution and legislation.